UPAYA PENERAPAN MEDIA PERMAINAN KARTU HURUF UNTUK MENINGKATKAN KEMAMPUAN MENGENAL HURUF PADA ANAK KELOMPOK B DI TK AISYIYAH BUSTANUL ATHFAL III - Yanti, Asma Asra; Margiani, Kristin; Neonufa, Samrid; G. Betty, Credo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the efforts of implementing letter card game media to improve letter recognition skills in Group B children at TK Aisyiyah Bustanul Athfal III. The main problems focused on are children who have not yet recognized letters and those who have difficulty arranging letters. This research employs a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. Data validity was ensured through technique triangulation. Data analysis used the Miles and Huberman model, which includes data collection, data reduction, data presentation, and conclusion drawing. The subjects of this study were all Group B teachers at TK Aisyiyah Bustanul Athfal III who directly stimulate children's letter recognition abilities. The results show that children's letter recognition skills have developed, as indicated by their improved ability to recognize, name, distinguish, and match letters. The implementation of letter card game media also helps create an interesting and enjoyable leaming atmosphere for children. In improving children's letter recognition skills, teachers undertake several efforts: (1) introducing letters through letter card games by showing the cards and explaining the shape and name of the letters; (2) guiding children to pronounce and repeat letters to facilitate memory and recognition; (3) inviting children to match letter cards with appropriate pictures or symbols to help them understand the relationship between letters and their meanings, (4) providing opportunities for children to play and interact directly with the letter cards to increase their activity and involvement, and (5) providing reinforcement and motivation during activities to build children's confidence in recognizing and naming letters. Keywords: Letter Card Game Media, Letter Recognition, Early Childhood